Karl Barth's Theology as a Resource for a Christian Theology of Religions - Ensminger, Sven (T&T Clark Studies in Systematic Theology, 2014)
This book uses Karl Barth's theology as a resource for Christian theology of religions. For this purpose, it examines Barth's theology under the doctrinal aspects of revelation, revelation and religion, theological anthropology and election, addressing questions such as the possibility of and context for revelation, Barth's understanding of religion, the theological approach to the human being, and soteriology. Furthermore, Barth's thought is put into conversation with other approaches in the field of theology of religions, notably Karl Rahner's inclusivism and John Hick and the pluralist para